Simulation-guided phase 3 trial design to evaluate vaccine effectiveness to prevent Ebola virus disease infection: Statistical considerations, design rationale, and challenges. (February 2016) - Vandebosch, An; Mogg, Robin; Goeyvaerts, Nele; Truyers, Carla; Greenwood, Brian; Watson-Jones, Debby; Herrera-Taracena, Guillermo; Parys, Wim; Vangeneugden, Tony
Starting in December 2013, West Africa was overwhelmed with the deadliest outbreak of Ebola virus known to date, resulting in more than 27, 500 cases and 11, 000 deaths. In response to the epidemic, development of a heterologous prime-boost vaccine regimen was accelerated and involved preparation of a phase 3 effectiveness study. While individually randomized controlled trials are widely acknowledged as the gold standard for demonstrating the efficacy of a candidate vaccine, there was considerable debate on the ethical appropriateness of these designs in the context of an epidemic. A suitable phase 3 trial must convincingly ensure unbiased evaluation with sufficient statistical power. In addition, efficient evaluation of a vaccine candidate is required so that an effective vaccine can be immediately disseminated. This manuscript aims to present the statistical and modeling considerations, design rationale and challenges encountered due to the emergent, epidemic setting that led to the selection of a cluster-randomized phase 3 study design under field conditions.